Climate amenities, climate change, and American quality of life - David Albouy; Walter Graf; Ryan Kellogg; Hendrik Wolff (Institute for the Study of Labor (IZA), 2013)
We present a hedonic framework to estimate U.S. households' preferences over local climates, using detailed weather and 2000 Census data. We find that Americans favor an average daily temperature of 65 degrees Fahrenheit, will pay more on the margin to avoid excess heat than cold, and are not substantially more averse to extremes than to temperatures that are merely uncomfortable. These preferences vary by location due to sorting or adaptation. Changes in climate amenities under business-as-usual predictions imply annual welfare losses of 1 to 3 percent of income by 2100, holding technology and preferences constant.
Keywords: H49; I39; Q54; R10; 330; climate amenities; climate change; quality of life; temperature profiles; heterogeneous preferences